The Analysis of Financial Performance Factors of Sharia Banking on Profitability before and during the Covid-19 Pandemic in Indonesia - Ayuningtiyas Ayuningtiyas; Irma Novida; Yeni Oktaviani (Jurnal Ekonomi Syariah Teori dan Terapan, 2022)
ABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui faktor-faktor kinerja keuangan yang mempengaruhi profitabilitas perbankan syariah. Metode yang digunakan dalam penelitian ini adalah deskriptif komparatif dengan pendekatan kuantitatif. Pendekatan kuantitatif menggunakan model Artificial Neural Network (ANN) dan menggunakan uji Wilcoxon. Penelitian ini menghasilkan variabel kinerja keuangan yang mempengaruhi profitabilitas pada masa sebelum pandemi yaitu CAR dengan nilai importance 71,619%. Sedangkan FDR yang menghasilkan nilai importance 0,447% dan NPF dengan nilai importance 27,932% tidak mempengaruhi profitabilitas. Sedangkan pada saat pandemi COVID-19, variabel kinerja keuangan yang mempengaruhi profitabilitas adalah variabel CAR dengan nilai importance sebesar 64,47%. Begitu pula pada variabel FDR yang memiliki nilai importance 35,37% melebihi 33,33% yang berarti varibel FDR sangat mempengaruhi profitabilitas. Hasil perbandingan kinerja keuangan sebelum dan pada saat pandemi menunjukkan terdapat perbedaan ROA, CAR, FDR, dan NPF sebelum dan saat pandemi COVID-19. Kata Kunci: Bank Syariah, Kinerja Keuangan, Profitabilitas, Pandemi COVID-19.   ABSTRACT The purpose of this study was to determine the factors of financial performance that affect the profitability of Islamic banking. The method used in this study is comparative descriptive with a quantitative approach. The quantitative approach uses the Artificial Neural Network (ANN) model and the Wilcoxon test. This study produces a financial performance variable that affects profitability in the pre-pandemic period, namely CAR with an importance value of 71.619%. While the FDR with an importance value of 0.447% and NPF with an importance value of 27.932% does not affect profitability. Meanwhile, during the COVID-19 pandemic, the financial performance variable that affects profitability is the CAR variable which produces an importance value of 64.47%. Likewise, the FDR variable which has an importance value of 35.37% exceeds 33.33%, which means that the FDR variable greatly affects profitability. The results of the comparison of financial performance before and during the pandemic show that there are differences in ROA, CAR, FDR, and NPF before and during the COVID-19 pandemic. Keywords: Islamic Banks, Financial Performance, Profitability, COVID-19 Pandemic.   DAFTAR PUSTAKA Achsani, M. N. F. F., & Kassim, S. (2021). The determinants of credit risk under dual banking system: indonesian experience based on bank specific variables. Al-Muzara'ah, 9(2), 215-229. https://doi.org/10.29244/jam.9.2.215-229 Almutairi, H. A. (2022). Covid-19 and its impact on the financial performance of kuwaiti banks: A comparative study between conventional and Islamic banks. The Journal of Asian Finance, Economics and Business, 9(1), 249–257. https://doi.org/10.13106/jafeb.2022.vol9.no1.0249 Almonifi, Y. S. A., Rehman, S. U., & Gulzar, R. (2021). The covid-19 pandemic effect on the performance of the islamic banking sector in KSA: An empirical study of al rajhi bank. SSRN. http://dx.doi.org/10.2139/ssrn.3834859 Bagaskoro, M. N., & Imansyah, M. H. (2019). Pengaruh ekspor impor terhadap transaksi berjalan indonesia sebelum dan sesudah subprime mortgage. JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2(2), 332-345. https://doi.org/10.20527/jiep.v2i2.1176 Bank Indonesia. (2020). Peraturan Bank Indonesia No. 22/6/PBI/2020 tentang perubahan kedua atas peraturan Bank Indonesia nomor 19/4/PBI/2017 tentang pinjaman likuiditas jangka pendek bagi bank umum syariah. Jakarta: Bank Indonesia. Retrieved from https://www.bi.go.id/id/publikasi/peraturan/Pages/PBI_221520.aspx. Culver, S. M. (2014). Effective higher education management through collaborative dual-degree programs. In S. Mukerji & P. Tripathi (Eds.), Handbook of research on transnational higher education (pp. 585-596). USA: IGI Global Csáji, B. C. (2001). Approximation with artificial neural networks. Unpublished master thesis. The Netherlands: Eindhoven University of Technology. Diah, A. (2021). Analisis kinerja perbankan syariah berdasarkan kegiatan usaha sebelum dan saat pandemi covid-19. Tesis tidak dipublikasikan. Purwokerto: UIN Prof. KH Saifuddin Zuhri Purwokerto. El-Chaarani, H., Ismail, T. H., El-Abiad, Z., & El-Deeb, M.S. (2022). The impact of covid-19 on financial structure and performance of Islamic banks: A comparative study with conventional banks in the GCC countries. Journal of Economic and Administrative Sciences, Vol. ahead-of-print(No. ahead-of-print). https://doi.org/10.1108/JEAS-07-2021-0138 Fakhri, U. N., Anwar, S., Ismal, R., & Ascarya, A. (2019). Comparison and predicting financial performance of islamic and conventional banks in Indonesia to achieve growth sustainability. Al-Uqud: Journal of Islamic Economics, 3(2), 174-187. https://doi.org/10.26740/al-uqud.v3n2.p174-187 Fakhri, U. N., & Darmawan, A. (2021). Comparison of Islamic and conventional banking financial performance during the covid-19 period. International Journal of Islamic Economics and Finance (IJIEF), 4(SI), 19-40. https://doi.org/10.18196/ijief.v4i0.10080 Fakhri, U. N., Anwar, S., & Ismal, R. (2019). Comparison of sharia and conventional banking bankruptcy rates in Indonesia. Tazkia Islamic Finance and Business Review, 13(2), 125-141. https://doi.org/10.30993/tifbr.v13i2.193 Farild, M., Bachtiar, F., Wahyudi, W., & Jannah, R. (2021). Analisis kinerja keuangan PT. BNI syariah tbk sebelum dan pada saat pandemi covid-19. Assets: Jurnal Ekonomi, Manajemen dan Akuntansi, 1(1), 88-95. Fatihudin, D., & Muchklas, M. (2018). How measuring financial performance. International Journal of Civil Engineering and Technology (IJCIET), 9(6), 553-557. Frida, C. V. O. (2020). Manajemen perbankan. Yogyakarta: Garudhawaca. Hartill, R. (2021). What is financial performance? Financial performance explained. Retrieved From https://www.thebalance.com/financial-performance-5193413. Ichsan, R. N., Suparmin, S., Yusuf, M., Ismal, R., & Sitompul, S. (2021). Determinant of sharia bank's financial performance during the covid-19 pandemic. Budapest International Research and Critics Institute (BIRCU): Humanities and Social Sciences, 4(1), 298-309. https://doi.org/10.33258/birci.v4i1.1594 Jamil, G. L. (2017). Numbers can restrict results?: Qualitative research methods as information and knowledge management support in supply chain and logistics sectors. In G. L. Jamil (Eds.), Handbook of research on information management for effective logistics and supply chains (pp. 1-22). USA: IGI Global. Kasmir. (2012). Analisis laporan keuangan. Jakarta: PT. Raja Grafindo Perkasa. Mujaddid, F., & Wulandari, S. (2017). Analisis faktor internal dan eksternal terhadap rentabilitas bank syariah di Indonesia. Jurnal Ekonomi Islam, 8(2), 202-218. Olivia, S., Gibson, J., & Nasrudin, R. A. (2020). Indonesia in the time of covid-19. Bulletin of Indonesian Economic Studies, 56(2), 143-174. https://doi.org/10.1080/00074918.2020.1798581 Otoritas Jasa Keuangan. (2011). Statistik perbankan syariah. Retrieved from https://www.ojk.go.id/id/kanal/syariah/data-dan-statistik/statistik-perbankan-syariah/Default.aspx. Otoritas Jasa Keuangan. (2016). POJK tentang kegiatan usaha dan jaringan kantor berdasarkan modal inti bank. Retrieved from https://www.ojk.go.id/id/kanal/perbankan/regulasi/peraturan-ojk/Documents/Pages/pojk-kegiatan-usaha-dan-jaringan-kantor-berdasarkan-modal-inti-bank/SALINAN-POJK.6%20BUKU.pdf. Otoritas Jasa Keuangan. (2019). Undang-Undang nomor 21 tahun 2008 tentang perbankan syariah. Retrieved From https://www.ojk.go.id/waspada-investasi/id/regulasi/Pages/Undang-Undang-Nomor-21-Tahun-2008-Tentang-Perbankan-Syariah.aspx. Otoritas Jasa Keuangan. (2021). Statistik Perbankan syariah 2019-2021. Retrievied from https://www.ojk.go.id/id/kanal/syariah/data-dan-statistik/statistik-perbankan-syariah/Default.aspx. Pravasanti, Y. A. (2018). Pengaruh NPF dan FDR terhadap CAR dan dampaknya terhadap ROA pada perbankan syariah di Indonesia. Jurnal Ilmiah Ekonomi Islam, 4(3), 148-159. http://dx.doi.org/10.29040/jiei.v4i03.302 Pringgabayu, D., Afgani, K. F., & Ricederia, A. (2021). Perbedaan NPF dan FDR bank muamalat antara sebelum dan selama pandemi covid-19. Jurnal Maps (Manajemen Perbankan Syariah), 4(2), 57-69. Riadi, E. (2016). Metode statistika parametrik dan nonparametrik untuk penelitian ilmu-ilmu sosial dan pendidikan. Tangerang: Pustaka Mandiri. Rini, N. (2018). The implementation of islamic corporate governance (ICG) on sharia banking in Indonesia. TIJAB (The International Journal of Applied Business), 2(1), 29-38. http://dx.doi.org/10.20473/tijab.V2.I1.2018.29-38 Rois, A. K., & Sugianto, D. (2021). Kekuatan perbankan syariah di masa krisis. Musyarakah: Journal of Sharia Economic (MJSE), 1(1), 1-8. Saputri, O., & Hannase, M. (2021). Pengaruh indikator makroekonomi terhadap kinerja keuangan bank umum syariah pada masa pandemi covid-19. Jurnal Tabarru': Islamic Banking and Finance, 4(1), 139-151. https://doi.org/10.25299/jtb.2021.vol4(1).6590 Somantri, Y. F., & Sukmana, W. (2019). Analisis faktor-faktor yang mempengaruhi financing to deposit ratio (FDR) pada bank umum syariah di Indonesia. Berkala Akuntansi dan Keuangan Indonesia, 4(2), 61-71. http://dx.doi.org/10.20473/baki.v4i2.18404 Supriadi, H. (2016). Metode penelitian untuk bisnis dan sosial. Yogyakarta: CV Budi Utama Vochozka, M., Horák, J., & Šuleř, P. (2019). Equalizing seasonal time series using artificial neural networks in predicting the Euro–Yuan exchange rate. Journal of Risk and Financial Management, 12(2), 1-17. https://doi.org/10.3390/jrfm12020076 Yunita, P. (2020). The future of Indonesia Islamic banking industry: Bankruptcy analyzing the second wave of global financial crisis. International Journal of Islamic Economics and Finance (IJIEF), 3(2), 199-226. https://doi.org/10.18196/ijief.3227